Application network programming method – knapsack problem and it’s modification - Burkova, Irina; Titarenko, Boris; Zheglova, Yulia (E3S web of conferences, 2023)
New method of multi-extremal optimization has been developed - a network programming method, which is based on the possibility to represent a complex function as a superposition of simpler functions. The paper deals with network (dichotomous) programming method and its application for solving multi-extremal and discrete optimization problems in Project Management. The main goal of the paper is to develop a new approach to solving knapsack problem and to solve a number of optimization problems of project building management. The optimal structure of the dichotomous representation is determined. On the basis dichotomous programming method new algorithm to solve a optimization problem is proposed